Strengthening and utilizing response groups for emergencies flagship: a narrative review of the roll out process and lessons from the first year of implementation - Conteh, Ishata Nannie M.; Braka, Fiona; Assefa, Edea Zewdu; Daniel, Ebenezer Obi; Ngofa, Reuben Opara; Okeibunor, Joseph C.; Omony, Otto Emmanuel; Hakizimana, Jean Leonard; Wondimagegnehu, Alemu; Djingarey, Mamoudou H.; Kobie, Aminata Grace; Kirigia, Doris Gatwiri; et al. (Frontiers in Public Health, 2024)
The World Health Organization Regional Office for Africa (WHO/AFRO) faces members who encounter annual disease epidemics and natural disasters that necessitate immediate deployment and a trained health workforce to respond. The gaps in this regard, further exposed by the COVID-19 pandemic, led to conceptualizing the Strengthening and Utilizing Response Group for Emergencies (SURGE) flagship in 2021. This study aimed to present the experience of the WHO/AFRO in the stepwise roll-out process and the outcome, as well as to elucidate the lessons learned across the pilot countries throughout the first year of implementation. The details of the roll-out process and outcome were obtained through information and data extraction from planning and operational documents, while further anonymized feedback on various thematic areas was received from stakeholders through key informant interviews with 60 core actors using open-ended questionnaires. In total, 15 out of the 47 countries in WHO/AFRO are currently implementing the initiative, with a total of 1,278 trained and validated African Volunteers Health Corps-Strengthening and Utilizing Response Groups for Emergencies (AVoHC-SURGE) members in the first year. The Democratic Republic of Congo (DRC) has the highest number (214) of trained AVoHC-SURGE members. The high level of advocacy, the multi-sectoral-disciplinary approach in the selection process, the adoption of the one-health approach, and the uniqueness of the training methodology are among the best practices applauded by the respondents. At the same time, financial constraints were the most reported challenge, with ongoing strategies to resolve them as required. Six countries, namely Botswana, Mauritania, Niger, Rwanda, Tanzania, and Togo, have started benefiting from their trained AVoHC-SURGE members locally, while responders from Botswana and Rwanda were deployed internationally to curtail the recent outbreaks of cholera in Malawi and Kenya.